Penyuluhan Pembuatan dan Penyemprotan Desinfektan pada Warga Desa Panca Jaya Kecamatan Muara Kaman - Siska Oktaviani; Destianti Catur Lia (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2022)
There are several ways that can be done to prevent the transmission of Covid-19, one of which is by spraying disinfectant in the surrounding environment and objects that are at risk of transmitting the virus. Making your own disinfectant at home can actually be done using ingredients that are household cleaning products. However, many people from Panca Jaya village, Muara Kaman sub-district, Kutai Kartanegara district, still don't know how to make a disinfectant, even if they know they generally just mix chemicals with water without knowing the content, properties and dosages that will be used to make the disinfectant. Seeing this in the field, it is necessary to have educational activities for the community regarding the manufacture of disinfectants. The purpose of this community service is to provide knowledge and understanding to the residents of Panca Jaya village about how to make disinfectants with home cleaning products in their respective homes. The method used in this counseling was to provide information via LCD and give out pamphlets to participants, demonstrate to make disinfectant, then continue spraying disinfectant in the surrounding environment. It is hoped that this activity can be applied in their daily life as a form of prevention and transmission of Covid-19.